A Critical Review on Superoxide‐Based Sodium–Oxygen Batteries. Issue 4 (21st September 2018) - Bi, Xuanxuan; Wang, Rongyue; Amine, Khalil; Lu, Jun
Abstract: Sodium superoxide (NaO2 ) based sodium–oxygen batteries (Na‐O2 ) possess high theoretical energy density and high energy efficiency that can be an alternative energy storage device to lithium‐ion batteries. However, the state‐of‐the‐art sodium–oxygen batteries are still far from real application due to the limited understanding of the cell chemistry and reaction mechanism. This article reviews the recent advances on NaO2 ‐based Na‐O2 batteries, especially focusing on the reaction mechanism and the stability of NaO2 . The parasitic reactions from the highly active NaO2 are discussed. It is hoped this provides insightful understanding on the mechanism and the role of the discharge product in Na‐O2 batteries. Abstract : In this mini review, an overview is presented of the recent advances on NaO2 ‐based Na‐O2 batteries, focusing on the reaction mechanism and the stability of NaO2 . The solution‐mediated pathway for the formation of NaO2 is discussed and parasitic reactions generated by NaO2 are also introduced here.